2018
DOI: 10.21271/zjpas.30.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, and Antimicrobial Activities of Phenolic and Flavonoid Rich Medicinal Plants (Fritillaria zagrica and Tulipa kurdica) Bulbs Collected in Kurdistan Region of Iraq

Abstract: Kurdistan is a closed and stored pool as a buried treasury industrial pharmacy. There are a large number of medicinal plants used in folk medicine by the traditional herbalists to treat varieties of human ailments. Among them, Fritillaria zagrica and Tulipa kurdica had been priced for their local traditional medicinal resources. Fritillaria zagrica Stapf. is a species very closely allied to F. tulipifolia and F. armena. Their flowers dark lurid untesselated, unchequered with a thick bloom outside, purple glauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…The presence of large amounts of phenolic compounds in the rice samples may contribute to their antioxidant activities and their ability to adsorb and scavenge free radicals [39]. This finding is in agreement with the findings of Aali et al [40]. Our results indicated that rice from the Harir subdistrict may contain compounds that may play a role as antioxidants, which in turn help in disease prevention.…”
Section: Polyphenolic Compounds In Rice Samplessupporting
confidence: 92%
“…The presence of large amounts of phenolic compounds in the rice samples may contribute to their antioxidant activities and their ability to adsorb and scavenge free radicals [39]. This finding is in agreement with the findings of Aali et al [40]. Our results indicated that rice from the Harir subdistrict may contain compounds that may play a role as antioxidants, which in turn help in disease prevention.…”
Section: Polyphenolic Compounds In Rice Samplessupporting
confidence: 92%